Gerakan Peningkatan Minat Baca Anak-Anak Masyarakat di Dusun Adong 1 Melalui Pembangunan Rumah Baca dan Penyediaan Buku Baca - Konstansia Hermiati; Siboro, Efrika; Nasri Tupulu; Bernadeta Ritawati; Erna Yatiningsih; Siskariyantif (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Adong 1 is one of the remote villages in West Kalimantan. Children's interest in reading in Adong 1 is still relatively low due to the lack of facilities for reading. Apart from that, people's mindset towards reading is also one of the factors causing children's low reading interest. People still think that reading is not important. Parents usually focus more on their children working in the fields. Therefore, this service focuses on building reading houses and providing reading books so that children interest in reading will improve. Activities are carried out in several ways, namely 1) preparation; 2) building reading houses;3)providing books;4) and forming the commitee. The results of the activity show that building a reading house and providing reading books can increase children's interest from an early age in Adong 1.